The Consolidated Medium-Term Income and Expenditure Framework. (Policy Papers; Policy Paper, 2011)
This paper updates the Fund's consolidated income and expenditure outlook from the projections in January 2011. The paper incorporates and extends the income and budget projections in the companion papers, Review of the Fund's Income Position for FY 2011 and FY 2012 (4/7/11) and FY 2012-FY 2014 Medium-Term Budget (3/31/11). The paper also provides an update on the projected accumulation of precautionary balances over the medium term. This responds to a request made during the September 2010 discussion of the adequacy of precautionary balances that progress towards targets be assessed also in the context of the annual income discussion.